2016
DOI: 10.12968/ijpn.2016.22.12.599
|View full text |Cite
|
Sign up to set email alerts
|

Definition of compassion in healthcare: a systematic literature review

Abstract: Compassion originates as an empathic response to suffering, as a rational process which pursues patients' wellbeing, through specific, ethical actions directed at finding a solution to their suffering. We therefore define the term compassion to mean the sensitivity shown in order to understand another person's suffering, combined with a willingness to help and to promote the wellbeing of that person, in order to find a solution to their situation. This should be a duty in healthcare professionals' daily work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 30 publications
2
81
0
8
Order By: Relevance
“…Recent studies demonstrate that patients experience empathy and compassion very differently from providers. Empathy emerges as a first stage of compassion, but then is followed by a motivation to change that suffering—and this is a second and distinct response that differs from empathy [33]. Compassion moves beyond empathy and includes a process of reacting, acknowledging, understanding, seeking help, performing actions aimed at a solution, and even receiving personal satisfaction [33].…”
Section: From Mutual Pretense (Empathy) To a Sustained Gaze (Compamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrate that patients experience empathy and compassion very differently from providers. Empathy emerges as a first stage of compassion, but then is followed by a motivation to change that suffering—and this is a second and distinct response that differs from empathy [33]. Compassion moves beyond empathy and includes a process of reacting, acknowledging, understanding, seeking help, performing actions aimed at a solution, and even receiving personal satisfaction [33].…”
Section: From Mutual Pretense (Empathy) To a Sustained Gaze (Compamentioning
confidence: 99%
“…Empathy emerges as a first stage of compassion, but then is followed by a motivation to change that suffering—and this is a second and distinct response that differs from empathy [33]. Compassion moves beyond empathy and includes a process of reacting, acknowledging, understanding, seeking help, performing actions aimed at a solution, and even receiving personal satisfaction [33]. Compassion departs from the empathy’s response to acknowledge and understand suffering, and adds the distinct features of being motivated by action and seeking small, supererogatory acts of kindness [34].…”
Section: From Mutual Pretense (Empathy) To a Sustained Gaze (Compamentioning
confidence: 99%
“…Free clinics operate with an underlying enthusiasm for compassion. Compassion is defined as a health professional's duty which involves understanding another person's suffering, combined with a willingness to help and to promote the wellbeing of that person, in order to find a solution to their situation [7]. Most of these clinics manage patients who present with chronic diseases such as hypertension, diabetes, hypercholesterolemia, etc., and studies have shown poor health and high dysfunctional levels in patients who attend free clinics when compared to those who do not [6,8,9].…”
Section: Free Clinicsmentioning
confidence: 99%
“…In contrast, compassion means to ‘share suffering, being in solidarity with persons and doing with one another’ (Doane & Varcoe, , 103–104). After a systematic review of 15 definitions, Perez‐Bret, Altisent, and Rocafort () defined compassion as ‘the sensitivity shown to understand another person's suffering, combined with a willingness to help and promote well‐being of that person, to find a solution to their problem’ (p. 605). This definition was adopted for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Only three schools explicitly described preparing students for patient‐centred care, which while aligns with compassion, is not conceptually congruent with compassionate care. Patient‐centred care comprises quality care through focus on patients’ needs in relation to their context (Lusk & Fater, ) and compassion is about sharing and alleviating their suffering (Perez‐Bret et al., ). The lack of attention regarding compassion by nursing schools is concerning as compassionate care is needed in every nurse‐patient interaction and there have been repeated calls to action to foster compassion in students.…”
Section: Introductionmentioning
confidence: 99%